The Effect Of Anemia Education Videos On Compliance Take Blood Booster Tablets - Handayani, Donna; Sumiati, Sumiati; Risnawati, Risnawati; Meihartati, Tuti (Program Studi Kebidanan Fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Latar Belakang: Proporsi remaja putri yang mendapat tablet tambah darah dalam 12 bulan terakhir sebesar 76,2%, namun hanya 1,4% remaja putri yang mengonsumsi tablet tambah darah sesuai anjuran. Cakupan pemberian Tablet tambah darah bagi remaja putri di Kalimantan Utara tahun 2022 sebesar 54,2% termasuk Kabupaten Tana Tidung. Upaya yang dapat dilakukan yaitu memberikan informasi tentang pentingnya pencegahan anemia serta konsumsi tablet tambah darah secara rutin. Salah satu media pemberian informasi yang menarik adalah video.Tujuan: Teranalisanya pengaruh video edukasi terhadap kepatuhan minum tablet tambah darah di SMPN 6 Tana Tidung.Metode: Penelitian kuantitatif dengan metode pre eskperimental design One group pretest and posttest. Populasi remaja putri SMPN 6 Tana Tidung. Sampel 143 remaja. Analisa data menggunakan Uji Wilcoxon.Hasil: skor mean kepatuhan remaja sebelum intervensi 1,15, median 1,00, SD 0,393 dan 95%CI antara 1,08-1,21. Setelah diberikan video edukasi, terjadi pengurangan dikategori tidak patuh dan terjadi peningkatan di kategori patuh dengan mean 1,32 dengan nilai median 1,00, SD sebesar 0,525 serta 95%CI antara 1,08-1,21. Hasil uji statisik didapatkan nilai p value = 0,000 (p value < 0,05). Uji Wilcoxon diperoleh nilai p-value 0.000. Kesimpulan: ada pengaruh video edukasi terhadap kepatuhan minum tablet tambah darah pada remaja putri di SMPN 6 Tana Tidung. Pengaruh video edukasi terhadap kepatuhan minum tablet tambah darah akan lebih baik bila disertai rutin konsumsi tablet tambah darah 1 kali setiap minggu disekolah dan dirumah. Kata Kunci : Anemia, remaja putri, tablet tambah darah, video edukasi ABSTRACT Background: The proportion of adolescent girls who received blood-boosting tablets in the last 12 months was 76.2%, but only 1.4% of adolescent girls took blood-boosting tablets as recommended. The coverage of giving blood booster tablets for adolescent girls in North Kalimantan in 2022 is 54.2%, including Tana Tidung Regency. Efforts that can be made are to provide information about the importance of preventing anemia and consuming blood supplement tablets regularly. One of the interesting information media is video.Purpose: To analyze the effect of educational videos on the adherence to taking blood supplement tablets at SMPN 6 Tana Tidung.Methods: Quantitative research with pre-experimental design method One group pretest and posttest. The population of adolescent girls at SMPN 6 Tana Tidung. A sample of 143 adolescents. Data analysis using the Wilcoxon Test.Results: adolescent median adherence score before the intervention 1.15, median 1.00, SD 0.393 and 95%CI between 1.08-1.21. After being given educational videos, there was a reduction in the non-compliant category and an increase in the compliant category with a mean of 1.32 with a median value of 1.00, elementary school of 0.525 and a 95%CI between 1.08-1.21. The results of the statistical test obtained a p value = 0.000 (p value < 0.05). The Wilcoxon test obtained a p-value of 0.000. Conclusion: there is an effect of educational videos on adherence to taking blood supplement tablets in adolescent girls at SMPN 6 Tana Tidung. The effect of educational videos on the adherence to taking blood supplement tablets will be better if accompanied by regular consumption of blood supplement tablets 1 time per week at school and at home. Keywords: Anemia, adolescent women, blood supplement tablets, educational videos